PENERAPAN EMOTIONAL FREEDOM TECHNIQUE (EFT) WITH VISUALITY UNTUK MENGURANGI KECEMASAN PADA KLIEN DISABILITAS RUNGU WICARA DI SEKOLAH LUAR BIASA NEGERI KAB. PATI, PROVINSI JAWA TENGAH - Agil Rizky Pranata; Meiti Subardhini; Krisna Dewi Setianingsih (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
SLB Negeri Pati is a special school owned by the government that provides educational services for people with hearing, speech and intellectual disability. In providing services for hearing-speech disability persons who have anxiety with various symptoms that arise, namely, easy to forget, difficult to concentrate, moody, easily tired, easily irritated, when meeting other people, choose to avoid, speak fast, and irregular breathing, besides that,its well known that the deaf-speech disability with all the limititations of hearing and speech devices causes psychosocial problems that the experiences such as; anxiety, fear, stress, maybe event trauma, all of which are difficult for others to know/understand. Through visually modified EFT, various psychosocial problems can be overcame, one of which is anxiety. The purpose of this study was to obtain an overview of the implementation of EFT-V towards reducing deafness anxiety at SLB Negeri Pati, The objectives are to find out a description of: 1. Characteristicsof research subjects; 2. Anxiety of hearing-speech disability before the implementation of EFTV; 3. Anxiety of hearing-speech disability after the implementation of EFT-V; 4. Implementation of EFT-V to overcome feelings of irritability with hearing-speech disability; 5. Implementation of EFT-V to overcome poor memory with hearing-speech disabiltiy; 6. Implementation of EFT-V to overcome moody behavior with hearing-speech disability. The method used in this study is a quantitative research of experimental research Reversal Single Subject Design (SSD). The result of the research is that EFT-V therapy is quite effective in reducing anxiety in hearing-speech disability based on the results of measurements using the HARS Scale. In addition, from the visual data analysis conducted, there are positive changes in target behavior that can be seen from the observation graph.